81.4k views
5 votes
Axis of symmetry: x = -0.5; Vertex: (-0.5, 0.75); f(x) = x2 + x + 1

Axis of symmetry: x = -0.5; Vertex: (-0.5, -0.75); f(x) = x2 - x + 1
Axis of symmetry: x = -0.5; Vertex: (-0.5, 0.75); f(x) = -x2 + x
Axis of symmetry: x = -0.5; Vertex: (-0.5, 0.75); f(x) = x2 + 2x + 1

Axis of symmetry: x = -0.5; Vertex: (-0.5, 0.75); f(x) = x2 + x + 1 Axis of symmetry-example-1
User Mike Menko
by
5.1k points

1 Answer

5 votes

Answer:

Option A: Axis of symmetry: x = -0.5; Vertex: (-0.5, 0.75); f(x) = x2 + x + 1

Explanation:

1) The axis of symmetry of quadratic graph is the vertical line that divides the graph curve into two congruent halves. In this case, it is: x = -0.5

2) Vertex is the point at which the graph curve changes direction or simply coordinates of the crest or trough of the curve.

The graph given has a trough with the coordinates: x = -0.5, y = 0.75. This is (-0.5, 0.75)

3) The roots of a quadratic equation are the points where the curve crosses the x-axis. In this case, it doesn't cross and so we have imaginary roots.

Now, formula for line of symmetry is; x = -b/2a

Thus; -b/2a = -0.5 or -b/2a = -1/2

Thus, b = 1 and a = 1

Our first and second terms will now be;

x² + x

Looking at the options, the only one with x² + x as it's first 2 terms is option A.

Thus, the complete equation will be x² + x + 1

User Moustafa Elqabbany
by
5.3k points